Investigação otoneurológica de sujeitos após acidentes vasculares cerebrais - Pimentel, Bianca Nunes (2017)
Introduction: Stroke is a vascular event that can bring about organic and functional changes, affecting negatively the quality of life. The difficulty in maintaining the postural balance is one of the main sequels. Objectives: investigate the postural balance and quality of life of subjects after ischemic and hemorrhagic stroke. Methods: Research approved by the Research Ethics Committee: CAAE 16728013.0.0000.5346. Patients underwent anamnesis, static and dynamic balance tests, motor coordination, Sensory Organization Test (SOT) by Foam-Laser Dynamic Posturography, Vectoelectronistomography Computerized and quality of life protocols Dizziness Handicap Inventory (DHI) and World Health Organization Quality of Life (WHOQOL)-Bref. Results: Twenty-five men (50%) and 25 women (50%) participated in the study, mean age was 63.24 years. All presented dizziness, mainly imbalance 41 (82%), type of ischemic stroke 42 (84%) and carotid artery 45 (90%). There was a high occurrence of changes in static and dynamic balance tests (between 40% and 96%). Significant differences were observed between dizziness handicap and elderly, schooling, type of stroke, visual complaints and changes in the tests of motor coordination and dynamic balance; between Whoqol-Bref domains and female, elderly, imbalance and circulation. All the SOT positions had a mean lower than the reference standard, with significant differences between position VI and visual preference with visual complaints; and significant relation between oculomotor tests with the caloric test of vectoelectronystagmography. Conclusion: All subjects complained of dizziness, mainly non-rotatory. The lower quality of life was related to women, elderly, with imbalance and visual complaints, as well as to changes in dynamic postural balance and motor coordination. Visual complaints were related to changes in visual preference in the foam-laser dynamic posturography, oculomotor testing and caloric testing of vectoelectronystagmography.